The Effectiveness Visual Feedback on Postural Control Post Stroke: Literature Review - Wanda Kurnia Yuda; Umi Budi Rahayu; Rivan Danuaji (Universitas Negeri Semarang, 2025)
Stroke often causes disturbances in the sensorimotor system, which can interfere with the sufferer's ability to maintain balance and movement. Visual feedback can provide real-time information regarding the position and movement of a patient's body after a stroke, by adjusting movement adjustments and controlling body posture to maintain balance. The aim of this research is to determine the effect of visual feedback from the exercises given on post-stroke patients' posture control related to muscle activity, center of pressure, balance, gait and functional ability. The method used is a literature review through searching Pubmed and Scopus articles with the keywords